PENGARUH POLITIK TERHADAP HUKUM - Puji Kurniawan (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2018)
Islam is the last religion of Allah SWT and the religion that was conveyed to the prophet Muhammad SAW through the angel Gabriel with the aim to change the human nature towards a better side by Allah SWT. Many ways are done by humans to achieve piety at His side or what is also called "politics". Because politics can be interpreted as a way to achieve certain goals. Not a few people consider that politics is something negative that must be shunned. Even though it should not always be like that, even politics is needed in religious life. For this reason, I hope to the reader, hopefully after reading or speaking this article is able to engage in politics in accordance with the Islamic religion